2018
DOI: 10.5194/hess-22-4699-2018
|View full text |Cite
|
Sign up to set email alerts
|

Modeling freshwater quality scenarios with ecosystem-based adaptation in the headwaters of the Cantareira system, Brazil

Abstract: Abstract. Although hydrologic models provide hypothesis testing of complex dynamics occurring at catchments, freshwater quality modeling is still incipient at many subtropical headwaters. In Brazil, a few modeling studies assess freshwater nutrients, limiting policies on hydrologic ecosystem services. This paper aims to compare freshwater quality scenarios under different land-use and land-cover (LULC) change, one of them related to ecosystem-based adaptation (EbA), in Brazilian headwaters. Using the spatially… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 68 publications
(89 reference statements)
1
15
0
2
Order By: Relevance
“…The thermotolerant coliforms presented, in general, smaller variation in the rivers with greater drainage areas (means of 5 to 9 10 3 CFU/100 mL) ( Table 2). Taffarello et al (2016) found a variation of thermotolerant coliforms from 14 CFU/100 mL to 1,000 10 3 CFU/100 mL in catchments with drainage areas between 10 and 1,000 km 2 in their study. In our research, drainage areas varied between 27 and 26,500 km 2 (Table 1), and the coliforms varied from <1 10 3 -3,300 10 3 CFU/100 mL.…”
Section: General Characterization Of the Datasetmentioning
confidence: 72%
See 4 more Smart Citations
“…The thermotolerant coliforms presented, in general, smaller variation in the rivers with greater drainage areas (means of 5 to 9 10 3 CFU/100 mL) ( Table 2). Taffarello et al (2016) found a variation of thermotolerant coliforms from 14 CFU/100 mL to 1,000 10 3 CFU/100 mL in catchments with drainage areas between 10 and 1,000 km 2 in their study. In our research, drainage areas varied between 27 and 26,500 km 2 (Table 1), and the coliforms varied from <1 10 3 -3,300 10 3 CFU/100 mL.…”
Section: General Characterization Of the Datasetmentioning
confidence: 72%
“…The different sizes of drainage areas and the contrasting land use types can significantly influence the quantitative and qualitative aspects of water resources. Taffarello et al (2016) observed significant correlations between nutrient loads and drainage areas in watersheds located in the Cantareira System (São Paulo and Minas Gerais States). The authors concluded that these results can serve as a basis for regionalization studies of pollutant loads and also to predict such loads and the pollution level in general affecting local aquatic systems.…”
Section: General Characterization Of the Datasetmentioning
confidence: 97%
See 3 more Smart Citations